1997
DOI: 10.1016/s0924-9338(97)80202-7
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic stability of ICD-10 psychiatric diagnoses in clinical practice

Abstract: This study examines the stability of ICD-10 diagnoses of patients admitted to Al Ain (United Arab Emirates) inpatients psychiatric unit during the period from November 1993 to August 1995. Diagnostic stability is a measure of the degree to which diagnoses remained unchanged at a later hospital admission. One hundred and seven patients were admitted more than once during this period, accounting for 168 readmissions. High levels of diagnostic stability were found for ICD-10 Fl-psychiatric disorders (100%), F2-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…Other conditions, including anxiety states, personality disorders and other psychoses were the least stable. Further stability studies have produced agreement with the high stability levels of schizophrenia, but have reported widely varying results for affective disorders and other conditions (Tsuang et al 1981 ;Lenz et al 1991 ;Marneros et al 1991 ;Rice et al 1992 ;Chen et al 1996Chen et al , 1998Daradkeh et al 1997).…”
Section: Introductionmentioning
confidence: 88%
“…Other conditions, including anxiety states, personality disorders and other psychoses were the least stable. Further stability studies have produced agreement with the high stability levels of schizophrenia, but have reported widely varying results for affective disorders and other conditions (Tsuang et al 1981 ;Lenz et al 1991 ;Marneros et al 1991 ;Rice et al 1992 ;Chen et al 1996Chen et al , 1998Daradkeh et al 1997).…”
Section: Introductionmentioning
confidence: 88%
“…Assuming that patients without a readmission had no further episode of severe mental illness and therefore retained the initial diagnosis of adjustment disorder, this finding would imply high diagnostic stability. Significantly lower stability rates were reported for diagnostic groups such as somatoform, generalized anxiety or panic disorders [26]. Due to the absence of a systematic follow-up procedure these conclusions should be taken with caution.…”
Section: Discussionmentioning
confidence: 99%
“…For the ICD-10 group of neurotic and stress related disorders combined a low level of diagnostic stability (37%) has found in contrast to a level of 73% for depressive disorders. However numbers were small and AD was not examined separately (Daradkeh et al 1997). Another study found that adjustment and anxiety disorders were the least stable at around 34% but again AD was not examined on its own (Huquelet et al 2001).…”
Section: Outcome and Prognosismentioning
confidence: 99%